Therapeutic feeding center in Sigi District: The challenges of reaching malnourished toddlers in mountainous areas - Lago, Rossalin (BKM Public Health and Community Medicine, 2021)
Objective : Malnutrition in children under the age of 5 years is one of the most common causes of morbidity and mortality. Every year more than 1 million children under five death because of severe acute malnutrition (SAM). Based on 2018 PSG data, malnutrion children in Indonesia are 17.70% spread across all provinces. Central Sulawesi with 13 districts/city contributed 19.6% of children under five with malnutrition and Sigi Regency recorded that 13.9% of children under five suffered from malnutrition in 2019. Content : One of the interventions carried out to overcome malnutrition is the Theurapeutic Feeding Center (TFC) program. TFC is a nutritional recovery tool that provides dietary and medical therapy for malnourished toddlers. In 2020 the Sigi Regency Government established a TFC at the Marawola Health Center which is located about 20 km from the district center. Marawola Health Center was selected as a TFC facility with consideration of trained human resources and supporting infrastructure. TFC Puskesmas Marawola currently serves malnourished toddlers from 176 villages in Sigi Regency. With the geographical condition of Sigi Regency which is a mountainous area, this could be a formidable challenge to bring service access closer. This study aims to analyze the challenges and obstacles to TFC services with targets scattered in mountainous areas and the solutions that have been carried out to bring services closer. Specifically, we will collect data from TFC officers, parents of malnourished toddlers who have been treated at TFC, parents of toddlers who refuse treatment, and authorized stakeholders. From these data, we can determine which solution to be taken to tackle the problems.